(3QSGdI Ydi NWHg eJf Cdajg GHf eGdcs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3Ef CHgi OQQ HfLhgG GdEfSGf bUOJ HgPg GdCfhGQ GdSfjI hGdCRgGQ GdHOjYjI GdHgjI TQM NWHI GdNdGUI GdCdajI TQMkG jJVef JdNjU eG hbY ddCTjGN ai ChdgG ef CSFdI hCLhHI s
(3BNQgG (B:s
(3hCeG HQGYI GdESJgdGd hgh Cf jHJOi HeG jOd Ydi ebUhOg hGdMeO ddg hMOg hGdUdGI hGdSdGe Ydi SjOfG eMeO fHjg hYHOg hYdi Bdg hUMHg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Hg eWGdH ddcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs